Drosophila Models Reveal Properties of Mutant Lamins That Give Rise to Distinct Diseases - Sydney G. Walker; Christopher J. Langland; Jill Viles; Laura A. Hecker; Lori L. Wallrath (Cells, 2023)
Mutations in the LMNA gene cause a collection of diseases known as laminopathies, including muscular dystrophies, lipodystrophies, and early-onset aging syndromes. The LMNA gene encodes A-type lamins, lamins A/C, intermediate filaments that form a meshwork underlying the inner nuclear membrane. Lamins have a conserved domain structure consisting of a head, coiled-coil rod, and C-terminal tail domain possessing an Ig-like fold. This study identified differences between two mutant lamins that cause distinct clinical diseases. One of the LMNA mutations encodes lamin A/C p.R527P and the other codes lamin A/C p.R482W, which are typically associated with muscular dystrophy and lipodystrophy, respectively. To determine how these mutations differentially affect muscle, we generated the equivalent mutations in the Drosophila Lamin C (LamC) gene, an orthologue of human LMNA. The muscle-specific expression of the R527P equivalent showed cytoplasmic aggregation of LamC, a reduced larval muscle size, decreased larval motility, and cardiac defects resulting in a reduced adult lifespan. By contrast, the muscle-specific expression of the R482W equivalent caused an abnormal nuclear shape without a change in larval muscle size, larval motility, and adult lifespan compared to controls. Collectively, these studies identified fundamental differences in the properties of mutant lamins that cause clinically distinct phenotypes, providing insights into disease mechanisms.